1968
DOI: 10.1029/ja073i003p00907
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Earth's bow shock and magnetic tail by Explorer 33

Abstract: The Explorer 33 satellite was launched July 1, 1966 and was injected into a highly elliptical earth orbit. The Goddard Space Flight Center magnetic field experiment onboard the spacecraft consists of a triaxial fluxgate sensor with a maximum dynamic range of ±64 gammas and a sensitivity of ±0.25 gamma along each axis. Because of the initial apogee‐earth‐sun angle of 118° west of the sun, the first 8 orbits of Explorer 33 (July 1 to November 11, 1966) mapped the earth's magnetosheath and magnetic tail from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
116
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(124 citation statements)
references
References 33 publications
7
116
1
Order By: Relevance
“…It was found that the field magnitude decreases with distance from the earth, with a gradient that can be described by an inverse power law (Behannon, 1968a;. The initially observed gradient has shown no statistically significant secular change ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that the field magnitude decreases with distance from the earth, with a gradient that can be described by an inverse power law (Behannon, 1968a;. The initially observed gradient has shown no statistically significant secular change ).…”
Section: Introductionmentioning
confidence: 98%
“…The early Explorer 33 data further suggested that the tail may not be c.Lrcular in cross-section but rather is elliptical with the major axis in the Z direction (Behannon, 1968a). All of these basic sm features of the tail field topology have been reviewed in detail by Ness (1969) and by Behannon and Ness (1969).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a circle or slightly elongated in the GSM z direction [Behannon, 1968[Behannon, , 1970Fairfield, 1971;Scarf et al, 1977]. Most empirical magnetopause models [e.g., Sibeck et al, 1991;Petrinec and Russell, 1996;Shue et al, 1997;Kawano et al, 1999] also adopted the hypothesis that magnetopause is rotational symmetric about the aberrated Sun-Earth line and has a rounded section at magnetotail.…”
Section: 1002/2013ja019257mentioning
confidence: 99%
“…See Ness (1969) for a comprehensive review of the experimental studies of the geomagnetic tail. Existence of an ordered tail and its imbedded neutral sheet was established by Explorer 33 to distances of 80 RE (Ness et al, 1967a, Behannon 1968Mihalov et al, 1968). At larger distances, the measurements by Pioneer 7 (Ness et al, 1967b;Wolfe et al, 1967) at 1000 RE suggested that certain of the observed field lines were connected to the earth in the shape of intermingled filamentary tubes.…”
Section: Introductionmentioning
confidence: 95%